The Effectiveness of the Internal Whistleblowing System in Fraud Detection and Prevention (Empirical Study at PT Asuransi Jiwasraya (Persero) - Hamilah, Hamilah; Suratman, Adji; Alam, Saeful (Dinasti International Journal of Economics, Finance & Accounting, 2022)
This research mainly aims to test and analyze the effectiveness of the Internal Whistleblowing System in Fraud Prevention. The population in this study are all employees who work in the Division of Finance & Accounting, Internal Audit PT. Asuransi Jiwasraya (Persero). While the sample used the purposive sampling method, amounting to 50 respondents. The independent/independent variables of the study are the influence of the Internal Auditor, Internal Control System, Whistleblowing System, Whistleblower Protection, Organizational Commitment. The dependent/dependent variable is Fraud Prevention. The research methodology uses Structural Equation Modeling (SEM) using smartPLS 3.2.7 software. The tests carried out are the Outer model, Inner model, indirect effect test, and hypothesis testing. The test results show the influence and significance of the internal control system on the prevention of fraud, the influence and significance of the internal auditor on the prevention of fraud, the influence and significance of the audit committee on the prevention of fraud, there is a significant effect of the independent commissioner on the prevention of fraud and there is a significant effect on the protection of the whistleblower on preventing fraud, there is a significant effect of the whistleblowing system on fraud prevention, there is a significant influence on the internal control system, internal auditors, audit committees, independent commissioners through the protection of whistleblowers against fraud prevention, and there is a significant influence on internal control, internal auditors, audit committees